2019
DOI: 10.1186/s12872-019-0999-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of timing on in-patient outcomes of complete repair of tetralogy of Fallot in infancy: an analysis of the United States National Inpatient 2005–2011 database

Abstract: Background This study aimed to investigate whether age at complete repair of tetralogy of Fallot (TOF) impacts postoperative morbidity and length of hospital stay in infants less than 365 days of age. Methods The United States Nationwide Inpatient Sample was searched for infants 0–365 days of age that underwent complete repair of TOF between 2005 and 2011. Patients were categorized based on age at time of repair: 0–30 days; 31–90 days; 91–180 days; > 180 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
2
6
1
5
Order By: Relevance
“…In our study, 125 children had complete repair of TOF at a median age of 4.4 years (IQR 3-5.7), with no mortality at 30 days after surgery. These are excellent results compared with the studies mentioned above and comparable to those of early complete repair of TOF [16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, 125 children had complete repair of TOF at a median age of 4.4 years (IQR 3-5.7), with no mortality at 30 days after surgery. These are excellent results compared with the studies mentioned above and comparable to those of early complete repair of TOF [16].…”
Section: Discussionsupporting
confidence: 78%
“…All of the other similar studies on late complete repair of TOF in children reported shorter lengths of stay, with ICU LOS ranging from a mean of 1.8 ± 1.2 days to 5 ± 3 days and hospital LOS ranging from a mean of 7.6 ± 3.8 days to 15 ± 7 days [8,9,13,15]. Outcome studies on complete repair of TOF in infancy show either comparable or shorter ICU and hospital LOS compared with our study [16,17,21,22]. We found no patient-related factors that could explain the higher ICU and hospital LOS in our study.…”
Section: Discussionsupporting
confidence: 70%
“…Most infants have surgical repair at 3-6 months of age [2]. An multivariate analysis showed that the risk of post-operative complications was 40% lower in infants ≥ 91 days old compared to those ≤30 days old [7].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention is usually performed in the first year of life, with the majority of repairs performed electively before age six months. If the RVOT obstruction is not critical, intracardiac repair is typically deferred until after the neonatal period not only to allow pulmonary vascular resistance to drop but also to give time to the infant to gain weight [23]. Neonatal surgical intervention may be needed in the setting of severe RVOT obstruction with or without ductal dependency [24].…”
Section: Discussionmentioning
confidence: 99%